2019
DOI: 10.21608/zvjz.2019.10214.1026
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Escherichia coli Strains Causing Respiratory Troubles in Chickens in Egypt

Abstract: Colibacillosis is a complicated disease causing severe economic losses and challenging veterinarians and producers. Therefore, this study aimed to characterize avian pathogenic Escherichia coli (APEC) strains causing respiratory signs in chickens. Thirty broiler chicken flocks at age of 17-35 days showed respiratory signs and greenish diarrhea during 2013-2016 outbreaks that occurred in Sharkia, Ismailia, Dakahlia and Sinai Governorates. The postmortem findings revealed typical colisepticemia picture including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
1
1
1
Order By: Relevance
“…Although the primary function was unclear Rodriguez-Siek et al, 2005;Hassan et al, 2020), they related to increased survival of bacteria and overcame the innate host serum immunity (Sedeek et al, 2020). The results observed no detection of both ompT and iss genes in E. coli isolated from collected samples and this is similar to the results obtained by Ibrahim et al (2019a), which recorded a similar percentage of E. coli isolating from the lung by PCR. The existing study's percentage disagreed with the percentages of 80.4% and 85.9% for ompT and iss genes, respectively reported by Mohamed et al (2018) and with 100% and 91% for both genes reported by Solà-Ginés et al (2015) and Subedi et al (2018) in APEC, respectively.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Although the primary function was unclear Rodriguez-Siek et al, 2005;Hassan et al, 2020), they related to increased survival of bacteria and overcame the innate host serum immunity (Sedeek et al, 2020). The results observed no detection of both ompT and iss genes in E. coli isolated from collected samples and this is similar to the results obtained by Ibrahim et al (2019a), which recorded a similar percentage of E. coli isolating from the lung by PCR. The existing study's percentage disagreed with the percentages of 80.4% and 85.9% for ompT and iss genes, respectively reported by Mohamed et al (2018) and with 100% and 91% for both genes reported by Solà-Ginés et al (2015) and Subedi et al (2018) in APEC, respectively.…”
Section: Discussionsupporting
confidence: 81%
“…The results showed 42% of the isolates from the lung and trachea by the conventional method. This percentage was more than the 31.7% recorded by Abd El-Aziz et al (2022) and less than 75.5%, 73.2% and isolated from broiler lung in other studies (Ibrahim et al, 2019a;2019b;Hassan et al, 2020).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation